Parametric Optimization of a Double Stage Reheated ORC for Recovering Waste Heat from a Combined Cycle Gas Turbine Power Plant in the Perspective of Repowering - Muhammad Reshaeel (00000319863); Dr. Adeel Javed (USPCAS-E, NUST, Islamabad, 2021)
TH-311
Keywords: MS-TEE Thesis